SCREENING SPONGES FOR BACTERIOCIDE TO BE USED IN SHRIMP CULTURE - Taufik Ahmad; Emma Suryati; Muliani Muliani (Research Center for Fisheries, 1995)
Sponges are suspected of having potential for producing bioactive material that canbe used for various purposes. The experiment aimed at identifying sponges which couldproduce bioactive materials for fish health management purposes